Compliance Risk Of Islamic Bank - Syarvina, Wahyu; Anggraini , Widia (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The implications of the risk of financial globalization and the impact of laissez-faire on the regulatory industry and Islamic finance companies serve to monitor aspects of Sharia compliance, prevent fraud and potential fraud in the real world and face the challenges of financial product innovation related to the adjustment of public services and the dynamics of the global economy. This is applied to prove that Islamic values can survive in the face of business competition, globalization of modern trade, and the sustainability of Islamic banking in Indonesia. The Sharia compliance alert function is in the form of actions, both preventive in nature and ensuring that policies, rules, systems and procedures as well as business activities are carried out by Islamic banks. In the end, Islamic banks need to understand all statutory provisions so that accountability and responsibility rests with every individual, from directors to the lowest bank employees. Likewise, innovations in Islamic bank products, especially sharia standards and sharia governance based on international standards, while still paying attention to the integrity and quality of Islamic bank human resources, carry out contracts and do not harm customers. Sharia compliance is important when Islamic banks cannot enforce Islamic values in global affairs and financial competition, which means they have not implemented and implemented Islamic values. These Islamic values must be accurate and remain relevant to time.